Efek Moderasi Karakteristik Ceo Perusahaan Mendunia Pada Hubungan Kualitas Informasi Akuntansi Dan Nilai Perusahaan - Muthmainnah; Yossi Diantimala; Riha Dedi Priantana (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: This study aims to examine whether CEO characteristics strengthen the effect of financial statement information quality on the firm value of well-known global companies. Methodology/approach: The sample is 366 well-known globally non-financial companies listed on the Asia Pacific Stock Exchange in 2019-2021. The sample was selected using a purposive sampling technique with criteria that companies’ annual and financial reports can be freely accessed. The analysis technique used is panel data regression analysis. Findings: The results show that the timeliness of financial reports and timely loss recognition significantly affect firm value. However, the effect of earnings management on firm value is not significant. Furthermore, CEO tenure, CEO gender, and CEO accounting education affect firm value significantly. This study contributes to the literature regarding the moderating effect of CEO characteristics in strengthening the effect of accounting information quality on firm value. Then it provides a view of the crucial effect of CEO characteristics in strengthening the impact of accounting information quality on a company's value. Practical Implication: Companies must pay attention to the financial report information and CEO characteristics such as CEO tenure, CEO gender, and CEO educational background in order to increase company value. Originality/value: This research is the first that examines the moderating effect of CEO characteristics on the impact of accounting information quality on the firm value of well-known global companies on the Asia Pacific Stock Exchange